Photocatalytic activity of semiconductor sulfide heterostructures - Raubach, Cristiane W.; De Santana, Yuri V. B.; Ferrer, Mateus M.; Buzolin, Prescila G. C. [UNESP]; Sambrano, Júlio R. [UNESP]; Longo, Elson [UNESP] (Royal Society of Chemistry (RSC), 2013)
This paper reports a theoretical and experimental study of the heterostructure photocatalytic activity in a CdS or ZnS and CdS@ZnS decorated system prepared by a microwave assisted solvothermal (MAS) method. A theoretical model of the decorated system was created in order to analyze the electronic transition mainly in their interface. The results show that CdS and ZnS interfaces produce an electron charge transfer from the CdS electron-populated clusters to the ZnS hole-populated clusters which helps to enhance the photocatalytic activity of the CdS@ZnS decorated system. © 2013 The Royal Society of Chemistry.
Keywords: CdS; Electron charge transfer; Electronic transition; Microwave assisted; Photocatalytic activities; Solvothermal; Theoretical and experimental; Theoretical models; Cadmium sulfide; Photocatalysis; Zinc sulfide; Heterojunctions